Temporal distribution of schedule‐induced behavior depends on the essential value of the reinforcer - Martínez‐Herrada, Antonio; Pellón, Ricardo; López‐Tolsa, Gabriela E. (Journal of the experimental analysis of behavior, 2025)
The development of schedule‐induced drinking depends on different variables affecting the food delivered at the end of the interfood interval. There are mixed results concerning the effects of varying magnitude and/or preference of different reinforcers in the development of schedule‐induced drinking, with some studies showing higher levels and other studies showing lower levels of drinking. The purpose of this study was to observe how differences in preference for a flavor of equally nutritious food pellets influence the development and maintenance of schedule‐induced drinking. Using the operant demand framework, four flavors of food pellets were compared to form two groups: one in which subjects would receive their most preferred flavor and another in which subjects would receive their least preferred flavor. In general, licking rates were lower and magazine‐entering rates were higher when the preferred flavor was delivered regardless of the fixed‐time schedule used. It is suggested that the value of the reinforcer has a larger influence on the immediately preceding behaviors, which will determine the distribution of competing responses in the interreinforcement intervals. These results are relevant to developing public policies that manipulate the taste of healthy food to increase its consumption.